Mirtazapine does not improve sleep disorders in Alzheimer's disease: results from a double‐blind, placebo‐controlled pilot study. Issue 2 (27th January 2016) - Scoralick, Francisca M.; Louzada, Luciana L.; Quintas, Juliana L.; Naves, Janeth O.S.; Camargos, Einstein F.; Nóbrega, Otávio T.
Abstract: Aim: The aim of this study was to test the efficacy and safety of mirtazapine in the treatment of sleep disorders in patients with Alzheimer's disease by means of a randomized, double‐blind, placebo‐controlled trial. Measurements were obtained for 7 days before intervention (baseline) and for 2 weeks after the onset of treatment. Methods: Alzheimer's disease patients with sleep disorders ( n = 24) received 15‐mg mirtazapine ( n = 8) or placebo ( n = 16) once daily at 2100 hours for 2 weeks. Patients were evaluated with actigraphy and structured scales before and after intervention. Historical control was employed. Results: Treatment with mirtazapine or placebo had no effect on cognitive and functional status as assessed by the Mini‐Mental State Examination and the Katz scale, respectively. There were no differences between groups in the frequency or severity of the adverse events reported. Compared with the placebo group, mirtazapine users showed increased daytime sleepiness but no improvement in the duration or efficiency of nocturnal sleep after treatment. Conclusions: This study showed no significant therapeutic effects of 15‐mg mirtazapine in community‐dwelling Alzheimer's disease patients with sleep disorders. Instead, this study found evidence of worsening of daytime sleep patterns.